2021
DOI: 10.1111/1346-8138.15816
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of bullous pemphigoid patients with versus without oral prednisolone treatment

Abstract: Bullous pemphigoid (BP) varies in severity and stratified treatments are needed. However, there are no definitive standards for choosing appropriate treatments. To elucidate the factors involved in choosing treatments and the clinical outcomes of BP, we retrospectively reviewed the clinical records of 78 BP patients at a single center. Of the 78 patients, 49 (62.8%) were treated with oral prednisolone (PSL) and 29 (37.2%) were treated without PSL. The patients with older age, lower Bullous Pemphigoid Disease A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A previous study reported that 18 cases (36.7%) out of 49 BP patients who were treated with systemic corticosteroids required adjuvant therapies. 21 Many of the patients in this study took 1.0 mg/kg/day of PSL and immunosuppressive agents in addition to corticosteroids as initial treatment, and these situations could have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that 18 cases (36.7%) out of 49 BP patients who were treated with systemic corticosteroids required adjuvant therapies. 21 Many of the patients in this study took 1.0 mg/kg/day of PSL and immunosuppressive agents in addition to corticosteroids as initial treatment, and these situations could have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…In clinically localized or mild cases, superpotent topical corticosteroids (clobetasol propionate) are applied to lesions only or to the whole body except the face as a first choice ( 215 , 216 , 220 ). Low-dose oral corticosteroids, tetracycline (and nicotinamide) and dapsone are also used.…”
Section: Autoimmune Skin Diseasesmentioning
confidence: 99%
“…Non-inferiority was shown in comparison with oral prednisolone (0.5 mg/kg/day), and the safety was significantly higher ( 223 ). Whilst all these treatments, especially those using topical or systemic corticosteroids, induce remission in over 90% of the patients within 4 weeks, relapses during tapering corticosteroids or after stopping treatment are frequent ( 220 , 222 , 224 ). This necessitates prolonged treatment with corticosteroids.…”
Section: Autoimmune Skin Diseasesmentioning
confidence: 99%